Students’ Practices with Examinations Cheating: Perspective of Students in Arsi University, Ethiopia - Moges , Birhanu (International Journal For Research In Educational Studies, 2020)
The main objective of the study was to assess the perception of instructors and students on the nature, practices, types and causes of examination malpractice. The study was basically employs cross-sectional survey research design using quantitative approach. The subjects were 60 instructors and 300 students who were selected randomly from four colleges. As self-developed questionnaire, which adapted from previously used to investigate practices, and methods of cheating examinations were used. The data was analyzed using statistical package for Social Sciences (SPSS) version 16.0. Results indicated that poor study habits, laziness, lack of self-confidence, the difficulty of the tests, lack of facilities, stiff competition and inadequate coverage of the course and the need of having extra points to raise their grades were as the cause of examination malpractice. Methods of cheating include bringing prepared answers to examination halls, writing on body parts and copying from someone else during a test are the top unethical behaviors. The respondents raised the following suggestions on how cheating may be curbed: strict supervision of examination, assisting learners to develop self confidence through delivering question based practical lesson, applying the rules and regulations strictly. Attention, therefore, needs to be given to strengthening and restoring a culture of integrity by heightening public awareness of the effects of fraud and corruption. The study recommended that there is need for thorough guidance and counselling and adequate preparation of students for examinations.